Protocol for an investigator-blinded, randomised, 3-month, parallel-group study to compare the efficacy of intraoperative tendon sheath irrigation only with both intraoperative and postoperative irrigation in the treatment of purulent flexor tenosynovitis. Issue 12 (15th December 2015) - Leppänen, Olli V; Jokihaara, Jarkko; Kaivorinne, Antti; Havulinna, Jouni; Göransson, Harry
Abstract : Introduction: The management of purulent flexor tenosynovitis of the hand consists of surgical debridement followed by antibiotic treatment. Usually, the debridement is carried out by irrigating the tendon sheath in a proximal to distal direction facilitated by two small incisions. It is unclear whether intraoperative irrigation by itself is adequate for healing or if it should be combined with postoperative irrigation in the ward. The hypothesis of this prospective randomised trial is that intraoperative catheter irrigation alone is as effective as a combination of intraoperative and postoperative intermittent catheter irrigation in the treatment of purulent flexor tenosynovitis. Methods and analysis: In this investigator-blinded, prospective randomised trial, 48 patients suffering from purulent flexor tenosynovitis are randomised in two groups. Intraoperative catheter irrigation of the flexor tendon sheath and antibiotic treatment is identical in both groups, whereas only the patients in one group are subjected to intermittent postoperative catheter irrigation three times a day for 3 days. The primary outcome measure is total active range of movement of the affected finger after 3 months of surgery. The secondary outcome is the need for reoperation. Ethics and dissemination: The research ethics committee of Pirkanmaa Hospital District has approved the study protocol. The protocol has been registered with ClinicalTrials.gov registry (#NCT02320929 ). All participants will give written informed consent. The study results will elucidate the role of postoperative irrigation, which can be criticised as being labour consuming and unpleasant to the patient. The results of the study will be disseminated as a published article in a peer-reviewed journal. Trial registration number: NCT02320929; pre-results.